2017
DOI: 10.1007/s00424-017-2047-2
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic receptors in adrenal chromaffin cells: physiological role and regulation of ion channels

Abstract: Adrenal medullary chromaffin cells in mammals are innervated by sympathetic preganglionic nerve fibers, as are sympathetic ganglion neurons. Acetylcholine in the ganglion neurons is well established as mediating fast and slow excitatory postsynaptic potentials through nicotinic and muscarinic acetylcholine receptors (AChRs), respectively. The role of muscarinic AChRs during neuronal transmission in chromaffin cells varies among different mammals. Furthermore, the ion channel mechanisms associated with the musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Although both AChR types can promote CA release, the reliance on stimulation via mAChRs or nAChRs is species dependent. For example in bovine adrenals, nAChRs are primarily responsible for cholinergic transmission and CA release, in chickens, the mAChRs are the key players, whereas in other species it could be both ( 142 , 171 173 ). Structurally, neuronal nAChRs are heterodimeric proteins made of 5 subunits, two α, and three β subunits, combinations of which can give rise to numerous receptor subtypes, with the α3β4 being the most pertinent nAChR for CA secretion ( 172 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both AChR types can promote CA release, the reliance on stimulation via mAChRs or nAChRs is species dependent. For example in bovine adrenals, nAChRs are primarily responsible for cholinergic transmission and CA release, in chickens, the mAChRs are the key players, whereas in other species it could be both ( 142 , 171 173 ). Structurally, neuronal nAChRs are heterodimeric proteins made of 5 subunits, two α, and three β subunits, combinations of which can give rise to numerous receptor subtypes, with the α3β4 being the most pertinent nAChR for CA secretion ( 172 ).…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, neuronal nAChRs are heterodimeric proteins made of 5 subunits, two α, and three β subunits, combinations of which can give rise to numerous receptor subtypes, with the α3β4 being the most pertinent nAChR for CA secretion ( 172 ). The nAChRs are ligand gated cation channels mediating quick excitation responses, while mAChRs are metabotropic receptors coupled with G-proteins resulting in slower neuronal signaling ( 172 , 173 ). There are 5 isoforms of the mAChRs, M 1 -M 5 , which are species specific and are coupled with different Gα proteins and signaling pathways ( 173 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acetylcholine released from the sympathetic preganglionic nerve fiber has been shown to mediate neuronal transmission through binding to the families of muscarinic acetylcholine receptors (mAChR) and nicotinic acetylcholine receptors (nAChR) in guinea pig adrenal medullary (AM) cells (Inoue et al, 2012). In addition, muscarinic receptor stimulation in AM cells of various mammals results in catecholamine secretion (Olivos and Artalejo, 2008;Inoue et al, 2018). The ionic mechanisms for muscarinic receptor-mediated excitation in AM cells differ among species of mammals, and their details have not yet been sufficiently elucidated (Inoue et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, muscarinic receptor stimulation in AM cells of various mammals results in catecholamine secretion (Olivos and Artalejo, 2008;Inoue et al, 2018). The ionic mechanisms for muscarinic receptor-mediated excitation in AM cells differ among species of mammals, and their details have not yet been sufficiently elucidated (Inoue et al, 2018). In rat AM cells, muscarinic M 1 receptor (also known as Chrm1) stimulation (Harada et al, 2015) induces the endocytosis of TASK1 (also known as Kcnk3) channels with a consequent decrease in K + channel activity Matsuoka and Inoue, 2017;Inoue et al, 2019b), whereas in guinea pig AM cells the muscarinic receptor-mediated excitation is ascribed to not only TASK1 channel inhibition, but also to nonselective cation (NSC) channel activation (Inoue and Kuriyama, 1991;Inoue et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…) and guinea‐pigs (Inoue et al . , ). We have reported that the mAChR‐mediated increase in excitability in rat (Inoue et al .…”
Section: Introductionmentioning
confidence: 99%